Donor insemination for heterosexual couples: A practice in transition - Naoaki Kuji; Ken Daniels (Reproductive Medicine and Biology, 2023)
Abstract Donor insemination (DI) has long been the treatment of choice for severe male infertility among heterosexual couples. Since disclosing when offspring become adults provokes serious emotional issues, counselors are recommending early disclosure about the treatment. Furthermore, several countries have changed their policies on nonanonymous sperm donation, concerning the strong demand of donor information from the offspring. There is a need for more research in psychosocial areas concerning DI treatment: especially to look at parents' roles (especially for infertile father) and their attitudes toward the need to use a donor to build their family.